Impact of learning effect on reliability factors and global indices in visual field testing by standard automated perimetry in normal healthy subjects and primary open-angle glaucoma patients to obtain an accurate baseline perimetry chart - Jagriti Rana; Anjali Singh; Arti Singh; Kamaljeet Singh; Shivangi Singh; Vineet Kumar Yadav (Indian Journal of Ophthalmology, 2023)
Purpose: To record and evaluate the reliability parameters (fixation loss (FL) %, false positive (FP) %) and global indices (mean sensitivity (MS), mean deviation (MD), pattern standard deviation in dB) in three visual field test sessions within two weeks to assess the learning effect in normal healthy subjects and POAG patients and comparison of learning effect gender wise and age wise in primary open-angle glaucoma (POAG) patients. Methods: This study was a prospective observational study. An oculus visual field testing was done and analyzed in 30 eyes of POAG patients and 30 eyes of normal healthy subjects in three visits. Results: There were 16 (53.3%) males and 14 (46.6%) females in the POAG group and 16 (53.33%) males and 14 (46.66%) females in the normal healthy subject group. A significant difference in data change between each visit in FL, FP, MD, MS was found though the difference was more pronounced in the second visit than in the third visit. The pattern standard deviation does not change significantly in subsequent visits in both groups. Gender wise and age wise no significant difference was found in the POAG group. Conclusion: Significant improvement in reliability parameters and global indices with each subsequent visit in both the POAG group and normal patients signifies the importance of learning effect on these parameters and the need to perform at least three tests to get the baseline perimetry chart, especially in POAG patients, while in normal subjects, second perimetric result can be accepted. It was also concluded that the learning effect is not influenced by age and gender.